New-dialect formation : the inevitability of colonial Englishes - Trudgill, Peter (Edinburgh : Edinburgh University Press, 2004)
This volume presents a new and controversial theory about dialect contact and the formation of new colonial dialects. It examines the genesis of Latin American Spanish, Canadian French and North American English, but concentrates on Australian and South African English.
Includes bibliographical references (pages 166-176) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
JSTOR
Keywords: English language -- Great Britain -- Colonies; English language -- Commonwealth countries; English language -- Great Britain -- Colonies -- Dialects; English language -- Dialects -- Commonwealth countries; English language -- Great Britain -- Colonies -- Variation; English language -- Variation -- Commonwealth countries; Languages in contact -- Great Britain -- Colonies; Languages in contact -- Commonwealth countries; English language -- 19th century -- History; Anglais (Langue) -- Pays du Commonwealth; Anglais (Langue) -- Dialectes -- Pays du Commonwealth; Anglais (Langue) -- Variation -- Pays du Commonwealth; Langues en contact -- Pays du Commonwealth; Anglais (Langue) -- 19e siècle -- Histoire; LANGUAGE ARTS & DISCIPLINES -- General; LANGUAGE ARTS & DISCIPLINES / Grammar & Punctuation; English language; English language -- Dialects; English language -- Variation; Languages in contact; Commonwealth countries; Taalvariatie; Engels; Diachronische taalkunde; 1800-1899; History